A tunable magnetic metamaterial based on the dipolar four-state Potts model. Issue 12 (December 2018) - Louis, D.; Lacour, D.; Hehn, M.; Lomakin, V.; Hauet, T.; Montaigne, F.
Abstract Metamaterials, tunable artificial materials, are useful playgrounds to investigate magnetic systems. So far, artificial Ising spin systems have revealed features such as emergent magnetic monopoles1, 2 and charge fragmentation3 . Here we present a metasystem composed of a lattice of dipolarly coupled nanomagnets. The magnetic spin of each nanomagnet is constrained to lie along a body diagonal, which yields four possible spin states. We show that the magnetic ordering of this metasystem (antiferromagnetic, ferromagnetic or spin ice like) is determined by the spin states orientation relative to the underlying lattice. The dipolar four-state Potts model explains our experimental observations and sheds light on the role of symmetry, as well as short- and long-range dipolar magnetic interactions, in such non-Ising spin systems. The four-state Potts model — where four individual states are accessible on each site — is studied using magnetic spins as state representations.